Função geradora : uma ferramenta de contagem - Machado, John William dos Santos (2015)
Counting techniques studied in basic education aim at the resolutions os simplest combinatorial problems. In this work, we present the generating functions, a powerful tool to solving more complex problems of counting. In this way, we discuss the contents of combinatorial analysis through the study of generating functions, proposing a didactic sequence on the subject for teachers of basic education can expand and diversify their teaching strategies, by means of this counting method.